Kinetic Resolution of dl-Hydrobenzoins Catalyzed by Copper(II) Complexes of C2-Symmetric Thiophene-Derived Ligands - Mansawat, Woraluk; Yukhet, Phanomsak; Bhanthumnavin, Worawan; Reiser, Oliver; Vilaivan, Tirayut (Synlett, 2022)
C2-Symmetrical chiral amino alcohol ligands with a central thiophene moiety were shown to be effective in combination with CuCl2 for the asymmetric acylation of dl-hydrobenzoins. In contrast to previously developed chiral ligands, readily available acetyl chloride and acetic anhydride can be used as reagents, in addition to benzoyl chloride, giving rise to the corresponding monoacylated products in up to 99% ee (S = 532).